Joint Interpretative Statements Of Investment Agreements: An Overview Of The Practice - Velly, Nicholas; Adolf, Huala; Amalia, Prita (Journal of Law, Politic and Humanities, 2025)
This article examines the role and practice of joint interpretative statements in investor state arbitration practices through a normative and comparative juridical analysis of arbitration cases, including NAFTA, EU, and other Cases. These joint interpretative statements clarify treaty ambiguities, align tribunal decisions with state intent, and offer cost-efficient alternatives to treaty renegotiation. However, their effectiveness is hindered by debates over whether they constitute genuine interpretations or disguised amendments, particularly when applied retroactively. Tribunals exhibit inconsistent acceptance, as seen in Pope & Talbot v. Canada, which resisted mid-dispute interpretations, and Methanex v. United States, which deferred to state intent under the VCLT. Regional shifts, such as the EU’s termination of intra-EU BITs, further complicate their application. The study argues that joint interpretations are still possible at helping state achieve interpretation in line with the treaty intent but require explicit treaty provisions on retroactivity, binding authority, and procedural triggers to enhance predictability. Balancing state sovereignty with investor protections remains critical, as tribunals must respect VCLT-guided state interpretations while safeguarding against arbitrary state overreach. The findings advocate hybrid mechanisms, such as multilateral advisory bodies, to harmonize interpretive practices and align ISDS with evolving global investment norms, emphasizing clarity in drafting and sustained dialogue between states and tribunals.